Teaching Through Stress Management and Stress Proofing - Sudharma, A.; V, Lekshmi (JOURNAL OF INDIAN EDUCATION, 2011)
Reaching stress-free situation demands a balancing between the schematic prioritisation of the contextuality of phenomenological confrontations and dimensionalities of instructional decisions. The shadowing of the designed modalities of stress symptoms and modes of stressors in teaching scenario lead towards the centrality of ineffective teaching syndrome. In order to equip the teachers with the proximal curriculum transaction skills, it is necessary to downsize the stressful situations through stress proofing tactics.